Forgiveness as a Factor of Adjustment in Bereaved Parents. Issue 2 (17th February 2020) - Záhorcová, Lucia; Halama, Peter; Enright, Robert D.
Abstract: The aim of this study was to focus on the relationship of forgiveness toward others, self-forgiveness, and anger toward God after the loss of a child. A sample of 84 grieving parents completed a battery of questionnaires. Self-forgiveness was found to be the strongest predictor of avoiding negative psychological adjustment after the loss (defined by the variables of normative and complicated grief, depression, anxiety, and anger) and the strongest predictor of positive psychological adjustment after the loss (defined by the variables of life meaningfulness, sense-making, benefit finding, and meaning reconstruction).